Pembuatan Cookies Udela Bebas Gluten Dan Kasein Berbahan Tepung Kombinasi Ubi Jalar Ungu, Kacang Gude, Labu Kuning Untuk Anak Autis - Sucitya Pratiwi; Made Darawati; igde Widiada; Irianto Irianto (Poltekkes Kemenkes Mataram, 2018)
Background. Children with autism are more often reported to have digestive problems. Gluten and casein are difficult to digest so autistic children must avoid preparations made from these two proteins. Maknan is quite popular with children including autistic sufferers, namely snacks such as cookies. But not many cookies are intended for autistic patients, cookies that do not contain gluten and casein. The goal is to determine the effect of a combination of flour (purple sweet potato, gude beans, pumpkin) on the organoleptic properties, nutritional content, and acceptance of udela cookies in autistic children Research Methods. The method used was a completely randomized design (CRD) with 4 levels of treatment each of 4 repetitions, namely a combination of flour (gude beans, purple sweet potato and pumpkin) t1 (30%; 30%; 40%), t2 (40% ; 30%; 30%), t3 (50%; 30%; 20%) and t4 (60%; 30%; 10%). Research Result. Combination of flour (purple sweet potato, gude beans and pumpkin) in udela cookies had a significant effect on color (p <α 0.05) but did not have a significant effect on texture, smell and taste (p> α 0, 05). Water content test results (5.15%), ash content (2.29%), protein (6.18%), fat (17.31%) higher than the quality requirements in Indonesian national standards and carbohydrates (69.09 %) lower than the quality requirements in Indonesian national standards. Test of acceptance of 9 people (60%) in the good category and 6 people (40%) in the less category. Conclusion. Based on the results of the research conducted. Autism that gets udela cookies given for a day shows that the category of autistic acceptance is included in the good category of (60%) and the category is less than (40%). In the category of less due to several factors such as autism, given cookies must adapt to new foods given and due to the study of 2 sick autistic children.